The citizen's guide to climate success : overcoming myths that hinder progress - Jaccard, Mark Kenneth (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2020)
"In the summer of 1990, as he announced his army's surprise invasion of Kuwait, the Iraqi dictator Saddam Hussein told his people that the neighboring oil-rich country was rightfully theirs. Many believed him. When he announced Kuwait's annexation, as Iraq's 19th province, they celebrated with patriotic fervor"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Energy policy; Climatic changes -- Government policy; Environmental policy; Environmental responsibility; Sustainable development